The Idiostyle of I. Puliui Through the Prism of the Linguistic Norm Dynamics (Case Study of the Thinker’s Letters) (Linguostylistic Studies, 2017)
The article explores I. Puliui’s individual style peculiarities in the context of the language norm dynamics. It covers basic parameters of the thinker’s orthographic and phonetic, morphological and syntactic, as well as lexical and semantic practices. The study affirms absolute peculiarity of the language proficiency of the leading representative of the south-western variant of literary Ukrainian language in the period of its final vernacular-based stage of codification. The author suggests diachronic and synchronic comparative analysis of the language norm dynamics according to the leading and the most complete lexicographical sources on the background of the tough social and political situation in Ukraine, when it was separated between Austria-Hungary and Russia. The study considers the lack of the unified literary norm of Ukrainian and the future perspective of the specific Ukrainian language norms reversion to modern coding.
Keywords: language norm dynamics; orthographic and phonetic, morphological and syntactic, lexical and semantic practices; synchronic and diachronic analysis